[Sea Rocks and City on Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of rocks and a city on Heimaey. A brown, rocky beach sits along a grey ocean where two jagged rock formations peek out of the water. White buildings with red roofs is visible in the background along a green hill. A green mountain with pointed sections along its top is visible in the background to the right.